2022
DOI: 10.1111/jnu.12766
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between occupational stress, sleep disturbance, and presenteeism of shiftwork nurses

Abstract: Purpose This study aimed to determine the relationships between occupational stress, sleep disturbance, and presenteeism in shiftwork nurses in South Korea. Design This cross‐sectional study used survey data from 442 shiftwork nurses at two hospitals in South Korea. Data were collected between March 2018 and April 2020. Methods A self‐reported questionnaire was used to assess shiftwork nurses’ demographic and job‐related information, presenteeism, occupational stress, and sleep disturbance. Data were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…According to Yang’s survey, heightened stress levels among health care workers reduce their work enthusiasm and increase the likelihood of presenteeism [ 26 ]. A study conducted in Korea revealed a positive correlation between occupational stress and presenteeism among shiftwork nurses [ 47 ]. Similarly, a survey on Korean occupational therapists indicated a strong association between stress and presenteeism, with presenteeism mediating the relationship between job stress and turnover intention [ 48 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Yang’s survey, heightened stress levels among health care workers reduce their work enthusiasm and increase the likelihood of presenteeism [ 26 ]. A study conducted in Korea revealed a positive correlation between occupational stress and presenteeism among shiftwork nurses [ 47 ]. Similarly, a survey on Korean occupational therapists indicated a strong association between stress and presenteeism, with presenteeism mediating the relationship between job stress and turnover intention [ 48 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Presenteeism is a common problem among healthcare professionals (Yang et al, 2016) and job stress is one of the important determinants of presenteeism. Studies conducted on healthcare professionals in the literature suggest that there is a significant positive relationship between job stress and presenteeism (Baek et al, 2022;Yang et al, 2017;Chun & Song, 2020). In addition, job stress is one of the important determinants of presenteeism and there is a mediating effect of presenteeism in the relationship between job stress and turnover intention.…”
Section: Mediating Effect Of Job Satisfaction and Presenteeismmentioning
confidence: 99%
“…Evidence shows that females might have more sleep problems than males, and married nurses were found to have shorter sleep duration and sleep latency compared to single nurses, which contributes to sleep problems (Van Nguyen & Liu (2022, Hwang & Yu (2021. Studies show that sleep problems are significantly associated with absenteeism and presenteeism (Firat, et al, 2019;Baek, et al, 2022). Firat and colleagues (2019) found that younger age and female gender were found to be associated with absenteeism, along with poor sleep quality.…”
Section: Literature Reviewmentioning
confidence: 99%